IMPLEMENTASI PEMBELAJARAN INTEGRATED ANTARA IMTAQ DAN IPTEK - Moh. Rifa’i (Nurul Jadid University, 2016)
Developments in science and technology have made the most of the human beings who forgot his nature. This not only applies to developed countries in the world, Indonesia as a developing country begins to feel the impact of this update. Science and Technology which was then known as the sci- ence and technology have changed the course of human earthly needs. The role of the school as one of the vehicles of educational development and characteristics of learners become the main focus for integrating science and technology capabilities of learners by side with IMTAQ. However, not all schools have the integrity to reconcile the two components, it is be- lieved that only faith-based formal education institutions that can meet the needs mentioned above. Imagine, a school-based religious or commonly known as madrassas is presenting religious superiority through subjects in the classroom and other learning activities by modifying the existing curriculum without changing the substance of the curriculum set by the government.